A-disciplinary considerations of two networks of local climate energy initiatives: Paper part of the Special issue entitled: "Unlocking Energies, Unpacking the Entanglements and Temporalities of Local Initiatives". Issue 11 (2nd November 2019) - Buschmann, Pia; Moser, Peter; Nadaï, Alain; Régnier, Yannick
ABSTRACT: In France and Germany, significant networks of local initiatives have developed around energy issues. This article brings practitioners' viewpoints into discussion. It presents the way in which two of these networks – the CLER-network for the energy transition (France) and the 100% – Regions network (Germany) – each identifies itself, describes its action and build-up process in relation to government action, and conceives of justice issues in the field of climate energy policy. The analysis shows that these two networks share a lot, including political ends (localisation of energy production, empowerment of rural territories), but practice quite differently as intermediaries for local initiatives. This suggests overcoming the transition management vs grassroots divide present in the literature and paying more attention to hybrids. It also brings emphasis on a type of intermediary's work, which has not been covered by the academic literature, namely that of tinkering with multiple supports and embedding action in local-national-supranational networking in order to maintain continuity. In discussing justice dimensions, we emphasize that motives or ends of action are only reflectively related to ideas of justice: justice issues seem bound up with a politics of assembling, either as a marker of federative action (all fighting for justice) or as a potentially divisive issue.